Direct reductive amination of aldehydes using lithium-arene(cat.) as reducing system. A simple one-pot procedure for the synthesis of secondary amines - Nador, Fabiana Gabriela (2012)
A simple one-pot procedure for the direct reductive amination of aldehydes using lithium powder and a catalytic amount of 4,4′-di-tert-butylbiphenyl (DTBB) or a polymer supported naphthalene as reducing system is described. The direct reductive amination of a variety of aldehydes with primary amines was achieved simply by adding a mixture of the corresponding carbonyl compound and the amine, over a solution of the lithium arenide in THF at room temperature. For most of the substrates tested the main reaction products were the secondary amines along with variable amounts of the corresponding alcohol and/or imine products. Theoretical DFT calculations have been applied in order to explain the differences in reactivity observed for aromatic substrates. © 2012 Elsevier Ltd. All rights reserved.